In vitro enzymatic synthesis of baccatin III with novel and cheap acetyl donors by the recombinant taxoid 10β-O-acetyl transferase. Issue 4 (4th July 2019) - You, Lin-Feng; Huang, Jia-Jun; Lin, Shu-Ling; Wei, Tao; Zheng, Qian-Wang; Jiang, Bing-Hua; Lin, Jun-Fang; Guo, Li-Qiong
Abstract: Despite the importance of baccatin III as a precursor to paclitaxel, a widely used chemotherapeutic agent, efficient enzymatic synthesis methods are lacking. Therefore, in this study, the recombinant taxoid 10β-O-acetyl transferase was prepared to produce baccatin III in vitro . The recombinant enzyme could use vinyl acetate, butyl acetate, sec -butyl acetate, isobutyl acetate, amyl acetate, and isoamyl acetate as novel and cheap alternative acetyl group donors to replace the expensive acetyl CoA for the enzymatic synthesis of baccatin III. A molecular docking study further confirmed that these acetyl donors could reasonably bind to the enzyme molecule. Using the aqueous two-phase bio-catalytic reaction system, hexane and ethyl acetate could increase the yield of product baccatin III by 2.8% and 1.1% respectively. This approach using novel and cheap acetyl donors is promising for the enzymatic synthesis of baccatin III for the future industrial production of paclitaxel.